2012
DOI: 10.5851/kosfa.2012.32.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Texture and Sensory Properties of Cream Cheese and Cholesterol-removed Cream Cheese made from Whole Milk Powder

Abstract: This study was aimed to compare the texture and sensory properties of Cream cheese and cholesterol-removed Cream cheese made from the whole milk powder (CRWMP) during storage at 7 o C for 4 wk. The cholesterol reduction by crosslinked β-CD was about 92% in CRWMP. In texture studies, hardness, gumminess, and chewiness had increased during the storage period of 4 wk in both cheeses, irrespective of treatment. In the sensory properties, cooked milk flavor was found to have decreased, whereas sourness had increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
5
10
0
Order By: Relevance
“…Slight differences (Table 1) with respect to fat (34.2 and 33.9%) and protein (8.7 and 8.65%) of RCC and CRCC were detected, which came in agreement with those obtained by Kim et al (2005), Han et al (2008) and Jeon et al (2012). The lower fat content of CRCC than the control might be due to less incorporation with casein via a fat-protein network as a result of probable modification of casein matrix by β-CD (Han et al 2008).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Slight differences (Table 1) with respect to fat (34.2 and 33.9%) and protein (8.7 and 8.65%) of RCC and CRCC were detected, which came in agreement with those obtained by Kim et al (2005), Han et al (2008) and Jeon et al (2012). The lower fat content of CRCC than the control might be due to less incorporation with casein via a fat-protein network as a result of probable modification of casein matrix by β-CD (Han et al 2008).…”
Section: Resultssupporting
confidence: 89%
“…Han et al (2008) achieved approximately 91% of cholesterol reduction in cream cheese using powdered or cross linked β-CD. Jeon et al (2012) showed that RCC contained 96.28 mg cholesterol/100 g, while CRCC contained only 7.47 mg/100g. Such different reduction rates could be attributed to the concentration of β-CD used, and to the conditions of applying β-CD, such as mixing temperature and temperature and time of the centrifugal force (Ahn and Kwak, 1999;Lee et al 1999Shim et al 2003 Yield and gross chemical composition of fresh cheese seem to be not affected by the treatment with β-CD.…”
Section: Sensory Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hundreds of types of cheese are produced in a range of flavours, textures and forms (Barry and Tamime 2010). Cream cheese is one of the most popular cheeses and is normally produced using fresh whole milk (Jeon et al 2012). Cream cheese is an acid coagulated, unripened, creamywhite cheese with a slightly acidic taste, a mildly diacetyl flavour, high moisture and high fat content (Kosikowski and Mistry 1997).…”
Section: Introductionmentioning
confidence: 99%